The myth of racial democracy in the labour market: A critical analysis of the participation of afro-descendants in brazilian companies - Machado Junior, Celso; Bazanini, Roberto; Ribeiro, Daielly Melina Nassif Mantovani (Organizações & Sociedade, 2018)
This research sought to identify the participation of different races in organizations and to investigate the opportunities for black people, in terms of employability and professional growth in Brazil. To meet this objective, documentary research was undertaken with 117 companies, which are among the 500 largest in Brazil. The results indicated that racial democracy is a myth in our society, hence the need to move forward with social policies that minimize inequalities between white and black people in the most significant company positions. The process of producing and reproducing racism continues to restrict the rise of black people to the highest hierarchical levels. In order to achieve equality for black people in the labour market, we must develop social policies with good intentions to the concept of praxis and be positioned among the benchmarks of militant sociology, establishing a set of affirmative government policies, accompanied by practices that encourage diversity in companies and denounce ideologies which reinforce the myth of racial democracy.